The Struggle for Abolition: Power and Legitimacy in Multilateral Nuclear Disarmament Diplomacy - Egeland, Kjølv (Taylor & Francis, 2025)
Can the genie be returned to the bottle? This book investigates the pursuit by states, civil society groups, and international organisations of nuclear abolition. Detailing the evolution of the institutional architecture for multilateral nuclear disarmament from the 1960s onwards, this book tells a story of high hopes, broken promises, and clashing views of history, security, and the future. Global nuclear politics deals in material power and security but is also shot through with contests over prestige, justice, and mutual recognition. Waves of innovation in multilateral nuclear disarmament diplomacy have typically come about on the back of crises of legitimacy within the broader nuclear order. The book concludes with a discussion of policy implications and a reflection on successes and failures in the history of multilateral nuclear disarmament. The volume will be of great interest to scholars and researchers of diplomacy, history, and politics and international relations.